Pengaruh Pendapatan Per Kapita, Belanja Daerah Sektor Kesehatan dan Belanja Daerah Sektor Pendidikan terhadap Indeks Pemabngunan Manusia di Kabupaten/Kota Provinsi Kalimantan Selatan Periode 2010-2018 - Ramadani; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The objectives in this study are (1) To find out whether Per capita Income, Health Sector Expenditures and Education Sector Expenditures Persistently Influential on Human Development Index in Regency / City of South Kalimantan Province for the period 2010-2018; (2) To find out whether Per capita Income, Health Sector Expenditure and Education Sector Expenditure Simultaneously Influence Human Development Index in Regency / City of South Kalimantan Province for the period 2010-2018; (3) To find out what variables are dominantly affecting the District / City Human Development Index of South Kalimantan Province 2010-2018. This research is expected to be able to provide understanding to local governments, private parties and community institutions with an interest in economic development in the regencies / cities of South Kalimantan Province. The results of this study indicate that per capita income has a significant effect and positive direction on the index of human development, regional spending on the health sector has a significant effect and a positive direction on the index of human development and regional expenditure on the education sector has a significant effect and positive direction on the index of human development.